Examining strategies for addressing high levels of “I don’t know” responding to risk perception questions for colorectal cancer and diabetes: An experimental investigation - Hay, Jennifer L. (Psychol Health, 2020)
OBJECTIVE: Many people say they “don’t know” their risk for common diseases (DK responders). Inadequate health literacy and higher disease information avoidance may suppress risk knowledge and thereby increase DK responding. Study goals were to examine two plausible interventions to address the health education needs of DK responders. DESIGN: Participants were identified in a pre-screener as DK responders for either diabetes or colorectal cancer (CRC) risk perception questions (N=1276; 35% non-white; 49% inadequate health literacy). They were randomly assigned to read either standard or low literacy risk information about diabetes or CRC, and to undergo a self-affirmation intervention or not. MAIN OUTCOME MEASURE: DK responding following reading the risk information. RESULTS: Neither intervention reduced DK responding. Multivariable analyses showed that health literacy, information avoidance, and believing the disease is unpredictable – but not risk factor knowledge and need for cognition – best predicted participants’ conversion from a DK response to a non-DK scale point response. CONCLUSION: Results confirm that both inadequate health literacy and higher information avoidance are associated with DK responding. DK responders are also disproportionately underserved and less adherent to health behaviors. Because galvanizing risk perceptions are central to public health, addressing their information needs is a priority.